The production of paper from sugarcane bagasse - Ahmad Nurhilmi Abdul Gani
In this final year project, sugarcane bagasse was evaluated as potential raw materials for pulp and paper production. Bagasse is the biomass remaining after sugarcane stalks are crushed to extract their juice. A sugar factory produces nearly 30 % of bagasse out of its total crushing.